The quest for quality project supervision: supervisor- supervisee relationship in the Education Faculty at Midlands State University in Zimbabwe - Mashingaidze, Samuel; Marimo, S. T. (Midlands State University, 2015)
The purpose of the study was to examine dissertation supervisor-supervisee relationship in the Faculty of Education at Midlands State University in Zimbabwe and identify preferred practice on the relationship. Various elements related to supervisor-supervisee relationship, the academic and personal relationship were dealt with. A mixed approachthat was descriptive in nature was employed while the instruments of the study were questionnaires and an interview. The sample comprised of 44 (21 post Advanced Level Bachelor of Education Honours and 23 post diploma Bachelor of Education students) and 13 (8 male and 5 female) Faculty of Education lecturers selected randomly. The results have shown a poor working relationship between supervisor and supervisee. Most of the students fail to meet submission deadlines due to inconsistencies in consultation. The study recommends the crafting of regulations that clearly guide and direct operations in student supervision to accommodate the preferred practice which should at least not disadvantage the student.